Termination Rules for Variable-Length CD-CAT From the Information Theory Perspective - Guo, Lei; Zheng, Chanjin (Frontiers in Psychology, 2019)
Cognitive diagnostic computerized adaptive testing (CD-CAT) aim to taking full advantages of both cognitive diagnosis (CD) and CAT. Cognitive diagnostic models (CDMs) attempt to classify students into several attribute profiles so as to evaluate their strengths and weaknesses while CAT system selects items from the item pool to realize that goal as efficiently as possible. Most of the current research focuses on developing the item selection strategies and uses a fixed-length termination rule in CAT. Nevertheless, a variable-length termination rule is more appropriate than the fixed-length rule in order to bring out the full potential of CD-CAT. The current study discussed the inherent issue of instability over different number of attributes with the previous termination rules, the Tatsuoka rule and the two-criterion rule, proposed three termination rules from the information theory perspective, and revealed the connection between the previous methods and one of the information-based termination rules would be discussed which further demonstrated the instability issue. Two simulation studies were implemented to evaluate the performance of these methods. Simulation results indicated that the SHE rule demonstrated strong stability across different number of attributes and different CDMs and should be recommended for application.